Desistance and victim protection: a narrative review of intersecting pathways in criminal justice reform - Mihăilă, Maria-Marinela (Technium Social Sciences Journal, 2025)
This narrative review explores the complex relationship between desistance from crime and the evolving practices of victim protection, emphasizing the need for integrative approaches in contemporary criminal justice systems. While the concept of desistance—referring to the process through which individuals cease offending—has gained significant traction in rehabilitation-focused policies, it often remains disconnected from the discourse on victims’ rights and needs. Drawing from recent interdisciplinary literature in criminology, restorative justice, and victimology, this review identifies key theoretical intersections, including the potential tensions and synergies between offender reintegration and victim safety. The analysis highlights how person-centered, trauma-informed, and community-based frameworks can foster both desistance and victim protection without compromising one for the other. Furthermore, the review examines the role of social support networks, institutional trust, and communication practices in managing these dual objectives. Ultimately, the paper advocates for a more balanced justice model that aligns offender reform with sustained victim empowerment and long-term societal resilience.